2004
DOI: 10.1002/agr.20022
|View full text |Cite
|
Sign up to set email alerts
|

Competitiveness and consumer preferences of U.S. fruits in Taiwan

Abstract: Taiwan is a major importing country of US fruits. This study examines the market competitiveness and consumer preferences of US fruits in Taiwan using cross-sectional data. Results indicate that for either retailers or consumers, imported US fruits compete favorably with domestic grown fruits in the Taiwanese fruit markets.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 15 publications
(13 reference statements)
0
2
0
Order By: Relevance
“…This research investigated the extent to which product familiarity affects purchasing imported fruit, in this case, the Korean pear in Taiwan. Asian pear is a popular fruit in Taiwan (USDA Foreign Agriculture Service, 2019), and certain characteristics of imported fruits like packaging, grading and product labels were preferred (Hsu and Wann, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…This research investigated the extent to which product familiarity affects purchasing imported fruit, in this case, the Korean pear in Taiwan. Asian pear is a popular fruit in Taiwan (USDA Foreign Agriculture Service, 2019), and certain characteristics of imported fruits like packaging, grading and product labels were preferred (Hsu and Wann, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…A previous study showed that market-oriented agribusinesses are highly innovative and achieve superior performance (Micheels & Gow, 2008). A well-balanced marketing plan emphasises overall superiority, and must be designed for both retailers and consumers (Hsu & Wann, 2004). Vertical coordination mechanisms must be installed in the marketing plan, leading to competition among retail chains and thus ensuring quality and building brand equity (Hanf & Kühl, 2005).…”
Section: Internal Environmentmentioning
confidence: 99%